Uric acid, neuroendocrine-immune complex and metabolism: relationships - Popovych, Igor; Bombushkar, Igor; Żukow, Xawery; Kovalchuk, Halyna (Journal of Education, Health and Sport, 2023)
Background. During the implementation of the project "Physiological activity of uric acid", our group discovered four variants of the combination of levels of uricemia and uricosuria in patients with chronic pyelonephritis in the remission phase, which are accompanied by characteristic constellations of parameters of the central and autonomic nervous, endocrine, and immune systems, as well as the exchange of nitrogenous metabolites and electrolytes, the levels of which correlate with uricemia and/or uricosuria. The aim of this study is to clarify the relationship between parameters of uric acid exchange and neuroendocrine-immune complex as well as other metabolites. Materials and methods. Under an observations were 34 males (23-70 years) and 10 females (33-76 years) with chronic pyelonephritis in the phase of remission. The main object of the study was serum and urine levels of uric acid. Other metabolic, endocrine and immune parameters were determined in the same blood and urine samples. In addition, EEG and HRV was recorded almost synchronously. Results. Among all registered parameters, 28 were identified as characteristic of the four variants of uric acid metabolism. The discriminant model includes, in addition to uricosuria and uricemia by definition, 10 neuroendocrine, 5 immune, and 6 metabolic parameters, as well as bacteriuria, Bifidobacteria of feces, entropy of immunocytogram and Popovych’s leukocytogram strain index. According to the results of the canonical correlation analysis, it was established that balneotherapy-induced concomitant changes in uricosuria and uricemia positively determine changes in, first, the PSD of the theta-rhythm in the T3 locus and beta-rhythm in the O2 locus aa well as HRV-markers of vagal tone and sympatho-vagal balance; secondly – diuresis and excretion of urea, magnesium, sodium, phosphates, calcium, potassium and chloride, as well as calciumemia and magnesiumemia; thirdly – serum IgG and CIC. Instead, changes in cortisolemia and testosteroneemia as well as TNF-alpha and the intensity of Staph. aureus phagocytosis are subject to negative determination. In general, the rate of uric acid determination of the dynamics of the listed parameters of the body is 96%. Conclusion. The uric acid molecule, as a structural analog of methylxanthines and adenosine, exerts effects on neurons, endocrinocytes, and immunocytes, presumably through their adenosine receptors, and the metabolic effects of uric acid are the consequences of its neuro-endocrine effects.